The effect of kappa-carrageenan and nisin on the physicochemical, mirobiological and sensory properties of kesong puti - Reyes, Jonah Aileen O.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
Kesong puti is a local unripened soft cheese that is produced from raw carabao?s milk and pasteurized cow or goat?s milk. As a product that has poor quality and short shelf life, improvement and shelf life extension of kesong puti is a significant issue in the dairy industry of the country. In this study, the effects of food additives such as nisin and kappa-carrageenan on the yield, physicochemical, microbial and sensory properties of kesong puti across storage days under refrigerated temperature were investigated. Modification of the base recipe of the National Institute for Molecular Biology and Biotechnology of the University of the Philippines-Los Bańos (NIMBB UPLB) was conducted by the addition of greater amount of fungal rennet and salt, standardization of coagulation and straining time of coagulum, and incorporation of biopreservative Nisaplin (Delvo® E-234) containing 2.5% nisin and different levels of semi-refined κ-carrageenan (MIOKA VU-4045) as stabilizer (0.00%, 0.10%, 0.25%, and 0.50%). Results obtained showed that κ-carrageenan was able to enhance the yield of kesong puti by as much as 69.75%, as well as significantly affect (P<0.05) its pH, syneresis, salinity, compressibility and color properties. Results gathered also showed that nisin at low levels (6 mgL-1) were able to reduce microbial load of kesong puti samples by as much as 79% for the first day of storage. In this research, control sample without κ-carrageenan and nisin had the lowest yield and shortest shelf life of only 5 days due to the development of an off-flavor as a result of proteolysis of the soft cheese. In addition, κ-carrageenan treated samples had a longer shelf life with the development of an off flavor occurring on the 3rd week of storage.
Thesis Classification: F
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Cheese -- Varieties -- Philippines